Congenital Perirectal Dermoid Cyst: A Rare Cause of Complex, Recurrent Pediatric Fistula-in-ano - Barry, Wesley E.; Asuelime, Grace E.; Zhou, Shengmei; Hammoudeh, Jeffrey; Ford, Henri R.; Kim, Eugene S. (Frontiers in Pediatrics, 2018)
Perianal abscess and fistula-in-ano are well-described in the pediatric population. They are most common in infants less than one year of age and often resolve with oral antibiotics; occasionally they require drainage or fistulotomy. The etiology is commonly associated with cryptoglandular obstruction and subsequent infection, however alternative diagnoses should be considered in cases of recurrent abscesses and fistulae that are refractory to standard treatments. In this report, we present the case of an 8-year-old boy with a complex, recurrent fistula-in-ano that resulted from a rare congenital perirectal dermoid cyst.